The Role of Government Expenditure on Per Capita Income Convergence in East Java Province - Hardianto, Erwin; Solihin, Achmad (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2024)
This research aims to test and analyze the absolute and conditional convergence of per capita income from 38 districts/cities in East Java with the variables PAD, BOS and BOK during the period 2020 - 2022. According to the Chow, Hausmann test and Lagrange Multiplier, the panel data convergence model estimates using the fixed effect model method. Results show that in the districts/cities and observation period, divergent conditions occurred. Also, conditional variables did not have a significant influence on the growth of per capita income. This condition can occur because capital and technology are distributed unevenly between districts/cities. The implication of this research is to improve the allocation and distribution of the government budget, especially those related to School Operational Assistance (BOS) and Health Operational Assistance (BOK).